PRODUCTION AND PROPERTIES OF RENNET FROM BUFFALO CALVES ABOMASAM - Ahmed; G.; S. A. Khan; M. Khaskheli; M. A. Qureshi; I. Ahmad (Journal of Animal and Plant Sciences, 2013)
Present study was planned to produce and evaluate liquid rennet from buffalo calves abomasa. Out of 30 abomasa collected, 20 samples were selected for the study and analyzed for proteolytic activity, clotting activity, productivity, shelf life, pH and sensory evaluation. Non protein nitrogen (NPN) contents of rennet coagulated milk (1.33±0.02%) were significantly higher (P 0.05) than that of cow milk (11014±2507.80). pH value of stored LMR (5.75±0.02) was significantly higher (P 0.05) in the score of color intensity of fresh (3.93±0.02) and stored rennet (3.88.±0.02). It was concluded from the study that liquid rennet can be prepared at local level with adequate clotting activity, better productivity and reasonable shelf life.
Keywords: Rennet; Calf abomasa; Chymosin; Clotting activity